ТАБИИЙ ГАЗНИ ФИЗИК – КИМЁВИЙ ХОССАЛАРИ ВА ИШЛАТИШ ИСТИҚБОЛЛАРИ - Махмудов, М.Ж.; муҳандислик, Бухоро; Ҳамроев, Р.Ж. (SCIENCE and SOCIETY, 2024)
The article provides information about the world’s natural gas reserves, their physico-chemical properties and prospects for the extraction, processing and use of natural gas.